2017
DOI: 10.1007/s11356-017-9117-z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption affinity and selectivity of 3-ureidopropyltriethoxysilane grafted oil palm empty fruit bunches towards mercury ions

Abstract: This study was conducted to investigate the potential application of oil palm empty fruit branches (OPEFB) as adsorbents to remove organic methylmercurry, MeHg(II), and inorganic Hg(II) from aqueous solution. The OPEFB was functionalized with amine containing ligand namely 3-ureidopropyltriethoxysilane (UPTES) aiming for better adsorption performance towards both mercury ions. The adsorption was found to be dependent on initial pH, initial concentraton, temperatures, and contact time. The maximum adsorption ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…It is worth noting that most adsorption studies related to PW in this work reported kinetics being very well described by pseudo-second order model as illustrated in the following references: [37][38][39]. To state this decisively, studies compared the fit of pseudo-first/second order, Elovich or intraparticle diffusion models when applicable as shown in these examples: [40][41][42][43].…”
Section: Kineticsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is worth noting that most adsorption studies related to PW in this work reported kinetics being very well described by pseudo-second order model as illustrated in the following references: [37][38][39]. To state this decisively, studies compared the fit of pseudo-first/second order, Elovich or intraparticle diffusion models when applicable as shown in these examples: [40][41][42][43].…”
Section: Kineticsmentioning
confidence: 91%
“…The adsorbents were observed in the literature to be sourced from either agricultural practices or the food chain waste. From agricultural practices, Elsherif et al [84] and Kunjirama et al [43] groups investigated the usage of plant branches for the adsorption of heavy metals. As described earlier, heavy metals are potential contaminants of PW depending on the location its produced at.…”
Section: Bio-adsorbentsmentioning
confidence: 99%
“…On the other hand, the extent of the metal ions adsorption was increased with the temperature and initial metal ions concentration. Alternatively, Kunjirama et al [41] carried out a study investigating the potential application of oil palm empty fruit bunches (OPEFB) as adsorbents to remove organic methylmercury, MeHg(II) and inorganic Hg(II) from aqueous solution. The OPEFB was functionalized with an amine-containing ligand namely 3-ureidopropyltriethoxysilane (UPTES) aiming for better adsorption performance towards both mercury ions.…”
Section: Bio-adsorbentsmentioning
confidence: 99%
“…The surface properties of SiO 2 layers can be affected by configuring siloxane layers with aminosilanes. , The performance of the siloxane layer is related to the properties of the amino groups. ,,, Among various aminosilanes, the ureido group contains two amines directly bonded to a carbonyl, with oxygen and nitrogen capable of donating lone-pair electrons. Such a structure enables it to possess a high number of hydrogen-bonding sites, facilitating the stable presence in the hot-concentrated PA solution and accessible adjacency to the silica surface for the ureidosilane. This characteristic makes the ureidosilanes more attractive than other aminosilanes for silica surface silanization. Thus, ureidosilanes show the potential to inhibit the SiO 2 etching by forming siloxane layers on the surface to prohibit the etchant from be accessed.…”
Section: Introductionmentioning
confidence: 99%